2019
DOI: 10.3856/vol47-issue2-fulltext-1
|View full text |Cite
|
Sign up to set email alerts
|

Bio mitigation based on integrated multi trophic aquaculture in temperate coastal waters: practice, assessment, and challenges

Abstract: In general, aquaculture wastes from traditional aquatic organism cultivation rapidly deteriorate the water quality of the surrounding ecosystems, endangering animals living in the area. The integrated multitrophic aquaculture (IMTA) system is a bio-mitigation strategy to alleviate the adverse impacts caused by aquafarming pollutants on the environment and aquatic species. This study provides an overview of the IMTA system, explains the interactive processes among the different trophic levels, summarizes the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
1
19
0
4
Order By: Relevance
“…While co-culture with finfishes brought in additional waste production from feces, the N and P levels in ponds remain optimal (Chopin et al 2012), as observed in this study. A similar concept was discussed by Zhang et al (2019) that feed species when co-cultured with nutrient absorbers like the M. modulaides, P. viridis, U. fasciata, and G. verrucosa can minimize the risk of eutrophication.…”
Section: Water and Soil Parametersmentioning
confidence: 93%
See 1 more Smart Citation
“…While co-culture with finfishes brought in additional waste production from feces, the N and P levels in ponds remain optimal (Chopin et al 2012), as observed in this study. A similar concept was discussed by Zhang et al (2019) that feed species when co-cultured with nutrient absorbers like the M. modulaides, P. viridis, U. fasciata, and G. verrucosa can minimize the risk of eutrophication.…”
Section: Water and Soil Parametersmentioning
confidence: 93%
“…It was supported by Chopin (2006), indicating that a culturing technology that mimics the natural ecosystem and its efficient recycling of energy and nutrient can be long-term sustainable. Zhang et al (2019) emphasized that integrated multitrophic aquaculture (IMTA) involves fed species with organic extractive species and inorganic extractive species that utilize wastes from aquaculture for their growth. It is engineered to utilize the uneaten feed at different trophic levels and convert the organic nutrient to an inorganic substance that can be used by the heterotrophs (Chopin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…MIMTA) demands creating a comprehensive database of individual-based sub-models for IMTA candidate organisms as recently suggested. 251 Thus, besides the need for aquafeed, marine macroinvertebrates may contribute to water quality close to aquafarms, in integrated mariculture composed of filter/deposit-feeding animals such as sponges and echinoderms. 252 For the sea cucumber Holothuria tubulosa as one of the most commercially exploited echinoderms, the ability of organic waste consumption from fish farms was recently described, making it a strong candidate for the potential development of IMTA in the Mediterranean region.…”
Section: Marine Side Streams (From Industry/discard): a Circular Aqua...mentioning
confidence: 99%
“…Some of these studies shown a tendency that the higher the feeding rate to a certain extent increases the growth performance, and decreases at a certain feeding rate. Therefore, more research is needed to know the optimal feeding rate for aquaculture species, specifically the Integrated Multitrophic Aquaculture (IMTA) model, whose system can recycle feed waste, such as feed waste and feces into a source of nutrition for other organisms [21][22][23]. There is still a lack of available information and knowledge on the feeding rate issue in IMTA.…”
Section: Introductionmentioning
confidence: 99%